Power and progress : our thousand-year struggle over technology and prosperity - Acemoglu, Daron; Johnson, Simon, 1963- (PublicAffairs, 2023)
"Two bestselling authors overturn conventional wisdom about how economies work, revealing the untold story of who wins and who loses the rewards of prosperity, in a work that fundamentally transforms how we look at and understand the world"--